1991
DOI: 10.1037/0022-006x.59.2.258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interparental violence on the psychological adjustment and competencies of young children.

Abstract: Preschool children (N= 107) were divided into 4 groups on the basis of maternal report: home and shelter groups exposed to verbal and physical conflict, a home group exposed to verbal conflict only, and a home control group. Parental ratings of behavior problems and competencies and children's self-report data were collected. Results show that verbal conflict only was associated with a moderate level of conduct problems; verbal plus physical conflict was associated with clinical levels of conduct problems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
202
3
15

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(228 citation statements)
references
References 25 publications
8
202
3
15
Order By: Relevance
“…14 However, it is not consistent with most studies investigating the association between IPV and behavioral disorders such as oppositional defi ant disorder or conduct disorder, 6,11,19 which have verifi ed this association.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…14 However, it is not consistent with most studies investigating the association between IPV and behavioral disorders such as oppositional defi ant disorder or conduct disorder, 6,11,19 which have verifi ed this association.…”
Section: Discussioncontrasting
confidence: 41%
“…20 A study conducted in SĂŁo Gonçalo, Southeastern Brazil, showed that 21.4% of schoolchildren between six and 11 years have been exposed to verbal or physical violence between their parents. 1 The impact of IPV on children's health is associated with trauma symptoms, 3,8,13 depression and anxiety, 13,18 aggressive behaviors, 6,18 behavioral disorders and poor school performance. 5 There is no consensus on the extent of this impact.…”
Section: Introductionmentioning
confidence: 99%
“…The area in which there is probably the greatest amount of information on problems associated with witnessing adult domestic violence is in the area of children's behavioral and emotional functioning. Generally, studies using the Child Behavior Checklist (CBCL; Achenbach & Edelbrock, 1983) and similar measures have found child witnesses of domestic violence to exhibit more aggressive and antisocial (often called "externalized" behaviors) as well as fearful and inhibited behaviors ( "internalized" behaviors) (Christopherpoulos et al, 1987;Davis & Carlson, 1987;Fantuzzo et al, 1991;Holden & Ritchie, 1991;Hughes, 1988;Hughes, Parkinson & Vargo, 1989;Jaffe et al, 1986;Jouriles, Murphy & O'Leary, 1989;Kerouac, Taggart, Lescop & Fortin, 1986;Stagg, Wills & Howell, 1989;Wolfe et al, 1985), and to show lower social competence than other children (Davis & Carlson, 1987;Fantuzzo et al, 1991;Stagg, Wills & Howell, 1989;Wolfe et al, 1985Wolfe et al, , 1986. Children who witnessed violence were also found to show more anxiety, selfesteem, depression, anger, and temperament problems than children who did not witness violence at home (Christopherpoulos et al, 1987;Forsstrom-Cohn & Rosenbaum, 1985;Holden & Ritchie, 1991;Hughes, 1988;Martin et al, 1987;Westra & Martin, 1981).…”
Section: Children's Problems Associated With Witnessing Violencementioning
confidence: 99%
“…17,[27][28][29][30] Children who live in homes with intimate partner violence (IPV), as well as other physical and verbal fighting in the home between family members, have higher rates of externalizing behaviors as well as clinical disorders. 27,28,[30][31][32][33][34] Emotion regulation and effortful control, two neurocognitive outcomes linked to externalizing behavior, are also compromised by IPV, with evidence suggesting that parenting can mediate this effect. 35 Such effects may be long lasting, with adults who were exposed to IPV and/or experienced physical maltreatment in childhood at increased risk for perpetrating IPV in adulthood.…”
mentioning
confidence: 99%